Analysis of Community Health Centers (Puskesmas) to Realize the Quality and Degree of Health Services for the Indonesian Community - Andiko Nugraha Kusuma (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Public health center is a health service facility that organizes public health efforts and first-level individual health efforts, by prioritizing promotive and preventive efforts, to achieve the highest degree of public health in its working area. who have healthy behavior (awareness, willingness and ability to live a healthy life); able to access quality health services, live in a healthy environment; and have optimal health degrees, both individuals, families, groups and communities. This research is a type of qualitative research, using descriptive method. The definition of qualitative research can be understood as a research procedure that utilizes data and has the aim of describing and analyzing events, social dynamics, phenomena and attitudes of individual and group perceptions of something. So, the results of this study explain that the community health center is a technical implementing unit of the district/city health office that is responsible for health development in its working area, besides that the institution also functions as a center for driving health-oriented development, a center for family and community empowerment and a service center. first star health. For this reason, in the context of realizing its functions, puskesmas have mandatory health activities/efforts consisting of maternal and child health and family planning (KB) efforts, health promotion efforts, environmental health efforts, efforts to improve community nutrition, prevention and eradication of infectious diseases. and basic treatment. As the technical implementing unit (UPTD) of the district/city health office, the puskesmas plays a role in carrying out some of the operational technical tasks of the district/city health office and is the first-level implementing unit and the spearhead of health development in Indonesia.